INNOVATIVE LEARNING STRATEGIES IN THE DIGITAL ERA - Daulat Marulitua Tambunan; Irwan Setiawan; Palima S.Sianipar (Adisam Publisher, 2025)
Technology is bringing a change in the learning paradigm through personalization, active engagement, accessibility, and flexibility. Students can learn independently and have more control over their learning process. Rapid feedback from technology enables a better understanding of students' strengths and weaknesses. Technology brings a change in the learning paradigm through personalization, active engagement, accessibility, and flexibility. Students can learn independently and have more control over their learning process. Rapid feedback from technology allows for a better understanding of a student's strengths and weaknesses. The research method in this article is the library method, which combines literature with field facts. The results of the literature study show that the use of technology can significantly influence student motivation through personalization, active involvement, accessibility, fast feedback, collaboration, innovation, choice, control, visual interest, and rewards. Digital era learning models include Flipped Learning, Blended Learning, E-Learning, and other innovative methods. The application of technology in learning has a positive impact, especially if combined with effective and inclusive learning strategies. Teachers must continue to develop their skills in adapting curriculum and learning methods. Innovative learning in the digital era is not only about the use of technology, but also the teacher's ability to create learning experiences that are interesting, interactive and relevant to technological developments.